Analisis Dampak Bauran Pemasaran Dalam Meningkatkan Volume Penjualan Pada Toko Aneka Di Singosari - RACHMAWATI, DITA; AMIR MAS'UD, ANUDIYAN (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
In general, research objectives include obtaining new knowledge or making discoveries. As proof or testing of the truth of existing knowledge. As a development of knowledge in an existing scientific field. The objectives that the researcher wants to express in conducting this research are to: 1) find out the marketing mix strategy implemented by the company. 2) Knowing the effect of the company's marketing mix on sales volume. Using a quantitative approach, researchers conducted research at Toko Aneka, which is located at Jl. Raya Singosari No. 69, Losari, Candirenggo, Kec. Singosari, Malang Regency, East Java 65153. From the results of the analysis, the influence of the marketing mix on sales volume can be seen using SPSS 17.0 tools. By using SPSS, it can be concluded that the F test shows a significance value of less than 0.05, which shows that the four indicators can influence sales volume. The results of the analysis from the T-test can be concluded that the four indicators that have significant value results are distribution, so it can be said that distribution can influence sales volume. Toko Aneka Elektronik needs to evaluate the marketing mix currently implemented, which has an insignificant influence on the volume of television sales in the Singosari area and its surroundings. For example, if the promotional activity carried out is personal selling, the company can use SPG staff as needed so that personal selling can run more effectively. And research needs to be done on promotions to increase sales volume. Distribution has a significant influence on the volume of television sales in the Singosari area and its surroundings; however, the vehicles used in distribution activities are only sedans and pickups. For this reason, Toko Aneka Elektronik can increase distribution by adding more vehicles for distribution activities.